Ultrasound evaluation of joint damage and disease activity in adult patients with severe haemophilia A using the HEAD‐US system. Issue 3 (23rd February 2021) - Jiménez‐Yuste, Víctor; de la Corte‐Rodríguez, Hortensia; Álvarez‐Román, María Teresa; Martín‐Salces, Mónica; Querol, Felipe; Bonanad, Santiago; Mingot‐Castellano, María Eva; Fernández‐Mosteirín, Nuria; Canaro, Mariana; Santamaría, Amparo; Núñez, Ramiro; García‐Frade, Luis Javier; et al.
Abstract: Introduction: The Haemophilia Early Arthropathy Detection with Ultrasound (HEAD‐US) system and scoring scale has proven to be an accurate and time‐efficient imaging method for identifying joint damage in patients with haemophilia. Aim: Observational, multicentre, cross‐sectional study conducted in 8 centres in Spain that assessed the joint status of adult patients with severe haemophilia A (SHA) using HEAD‐US. Methods: Joint status of the elbow, knee and ankle was evaluated in adults with SHA receiving on‐demand (OD) treatment, or primary (PP), secondary (SP), tertiary (TP) or intermittent (IP) prophylaxis. Results: Of the 95 patients enrolled, 87 received prophylaxis (6.3% PP, 38.9% SP, 43.2% TP and 3.2% IP). Mean age was 35.2 years, and 59% of patients had not undergone image testing in the last year. The HEAD‐US score was 0 in all joints in 6.3% of patients. The ankle was the most affected joint, regardless of treatment regimen. Patients receiving OD treatment, TP or IP had the overall worst scores, mainly in the ankles and elbows; a similar but milder profile was observed in patients on SP; and patients on PP had the best score in all joints. Conclusion: Joint function may be effectively preserved in patients with SHA on PP, but OD treatment or later initiation of prophylaxis does not seem to prevent progression of arthropathy. Disease worsening was observed in patients OD, TP or IP, most often affecting ankles and elbows. Closer ultrasound imaging monitoring may improve management of these patients.